Allocation of infrastructural facilities - Olaf Hübler (Intereconomics, 1975)
Problems of geographical distribution of infrastructural facilities in LDCs cannot be tackled without reference to development strategies. This should mainly be based on the answer to the question whether development ought to radiate from a given centre of growth, or whether a broader distribution over the whole territory is preferred.
Keywords: 330; Development Strategy